The design history reader - Lees-Maffei, Grace; Houze, Rebecca (Berg Publishers, 2010)
"This is the first anthology to address Design History as an established discipline, a field of study which is developing a contextualised understanding of the role of design and designed objects within social and cultural history. Extracts range from the 18th century, when design and manufacture separated, to the present day. Drawn from scholarly and polemical books, research articles, exhibition catalogues, and magazines, the extracts are placed in themed sections, with each section separately introduced and each concluded with an annotated guide to further reading. Covering both primary texts (such as the writings of designers and design reformers) and secondary texts (in the form of key works of design history), the reader provides an essential resource for understanding the history of design, the development of the discipline, and contemporary issues in design history and practice. Selected authors: Judy Attfield, Jeremy Aynsley, Rayner Banham, Roland Barthes, Jean Baudrillard, Walter Benjamin, Pierre Bourdieu, Christopher Breward, Denise Scott Brown, Ruth Schwarz Cowan, Clive Dilnot, Buckminster Fuller, Paul Greenhalgh, Dick Hebdige, Steven Heller, John Heskett, Pat Kirkham, Adolf Loos, Victor Margolin, Karl Marx, Jeffrey Meikle, William Morris, Gillian Naylor, Victor Papanek, Nikolaus Pevsner, John Ruskin, Adam Smith, Penny Sparke, John Styles, Nancy Troy, Thorstein Veblen, Robert Venturi, John Walker, Frank Lloyd Wright"--Provided by publisher.